Influence mechanism and impacting boundary of workplace isolation on the employee's negative behaviors - Yang, Ya-Juan; Lu, Lei (Frontiers in Public Health, 2023)
Introduction Based on social identity theory, by introducing organizational identification as mediating variable and identification orientation as moderating variable, this paper studies the influence mechanism and impacting boundary of workplace isolation on employee fatigue and turnover intention. Methods Based on logic relationship, seven basic hypotheses are put forward to construct the theoretical model of the problem. Based on the 300 effective questionnaires being obtained from employees in Mainland China, the empirical investigation adopts the three-phase lag time design. By regression analysis and bootstrap test. Results (1) Workplace isolation has a significant positive effect on employee's work fatigue; (2) Workplace isolation has a significant positive effect on employee's turnover intention; (3) Organizational identification plays a partial mediating role between workplace isolation and work fatigue; (4) Organizational identification plays a partial mediating role between workplace isolation and employee's turnover intention; (5) Employee identification orientation negatively moderates the relationship between workplace isolation and organizational identification, that is to say, the higher the degree of identification orientation, the more inhibited the negative impact of workplace isolation on organizational identification; (6) Employee identification orientation has a negative moderating effect, namely, compared with the low degree of employee identification orientation, the higher the employee identification orientation, the positive effect of workplace isolation on work fatigue and turnover intention through organizational identification become weaker. Discussion Understanding these influencing mechanisms will have a great influence on guiding managers to mitigate the negative effects of “workplace isolation” in practice and improve the work efficiency of employees.